Analisis Penawaran Tenaga Kerja terhadap Kegiatan Non Usaha Tani oleh Rumah Tangga Tani: Studi Kasus di Kecamatan Wonosari Kabupaten Gunungkidul Propinsi Daerah Istimewa Yogyakarta - Sunarto, Sunarto; Nachrowi, Nachrowi D. (UI Scholars Hub, 2008)
The main purpose of this research is to investigate the factors influencing the labor supply on the non-agricultural activities and the effect of income from non-agricultural activities to the structure and distribution of farmer household income. To reach the goals, three models are developed. The first and second models are labor supply models of husband and wife, respectively. For both models, the dependent variables are labor supplies proxied by work-hours of non-agricultural activities per year. While the independent variables for both models are area of land used, wage level in non-agricultural, age, number of household member with age above and below 5 years, number of working household members, and location of the household. The third model is a model with contribution of non-agricultural income as its dependent variable, while its independent variable is area of land used. The data source for this research is taken from a primary survey, while the secondary data gathered from BPS in Gunung Kidul. The study shows that husband labor supply on non-agricultural activities is affected by the area of land used, wage level, education level, number of household members, and household location. But, education level and number of working household members are not giving significant influence to husband labor supply on non agricultural sectors. Furthermore, wife labor supply is influenced by the area of land used, wage level, age, education level, number of household members with age below 5 years, and household location. In the contrary, number of household members ofage over 5 years and number of working household members aren't seem to have significant effect on wife labor supply model on non agricultural activities.